Financial policy and economic growth : the Lebanese experience - Makdisi, Samir A. (New York : Columbia University Press, 1979)
This book focuses on financial policy to economic and to economic growth with reference to the Lebanese experience during the 1945-74.According to the book, Lebanese economic policy until 1974 had two main objectives: (1) to maintain relative financial stability and (2) to support the economic efforts of the private sector and provide it with opportunities to exercise the major influence on the rate and pattern of economic expansion. To achieve the first objective, two means were employed: (a) a liberal trade and payments regime and (b) a flexible exchange. The book is divided into two parts: part 1, policy framework and developments in the monetary and exchange fields; and financial policy and economic growth, an evaluation.
Includes index.
Bibliography p. 199-203.
lje 16/10/18
Loans
Keywords: Finance; Monetary policy; Lebanon